2011
DOI: 10.5006/1.3628683
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Behavior of Different Metallic Materials in Supercritical Carbon Dioxide at 550°C and 250 bars

Abstract: In the framework of a new generation of nuclear reactors, typically sodium fast reactors, supercritical carbon dioxide (CO 2 ) with a Brayton cycle (at 550°C and 250 bars) is identified as a promising energy conversion system to replace the traditional steam generators. Nevertheless, the long-term integrity of the heat exchanger structure in this environment has to be proven over at least 20 years. To this purpose, the corrosion behavior of different metallic materials under static CO 2 at 550°C and 250 bars i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 19 publications
1
50
0
Order By: Relevance
“…So far, many researches of the 21Cr‐11Ni type steel which focused on the reliability assessment for the service properties, such as creep, oxidation, hot corrosion, etc. have been reported . Earlier work by the present authors found that the hot workability of the steel was closely associated with the deformation temperature which can cause the formation of DRX and moreover, that RE element yttrium could eliminate the sulfur segregation on the grain boundary which can significantly improve the hot ductility at lower temperatures.…”
Section: Introductionsupporting
confidence: 54%
“…So far, many researches of the 21Cr‐11Ni type steel which focused on the reliability assessment for the service properties, such as creep, oxidation, hot corrosion, etc. have been reported . Earlier work by the present authors found that the hot workability of the steel was closely associated with the deformation temperature which can cause the formation of DRX and moreover, that RE element yttrium could eliminate the sulfur segregation on the grain boundary which can significantly improve the hot ductility at lower temperatures.…”
Section: Introductionsupporting
confidence: 54%
“…However, combustion impurities in the sCO 2 are a concern. With ppm level of impurities, typical of indirect cycles, most sCO 2 compatibility studies have shown protective behavior for highly alloyed Fe‐ and Ni‐base structural alloys . Nevertheless, commercial sCO 2 systems may start with lower purity CO 2 compared to what is used in most laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Impurities could also assist in C permeating the protective surface oxide (either Cr 2 O 3 or Al 2 O 3 ). Whereas 9%Cr steels have shown severe internal carburization, higher alloyed materials at higher temperature have not shown much carbon ingress …”
Section: Introductionmentioning
confidence: 99%
“…Previous and current sCO 2 studies as a function of CO 2 temperature and pressure. Diamonds show prior exposures at CEA , INL , MIT , and Wisconsin , stars show prior ORNL studies and circles show current conditions. The design limits of the alloy 282 autoclave are shown for reference…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate the limited sCO 2 data available above 700 8C and 200 bar, the diamond symbols in Fig. 3 attempt to summarize the conditions explored in previous sCO 2 compatibility evaluations [11][12][13][14][15][16][17][18][19][20][21]. In the presence of CO 2 , there is a concern about internal carburization (despite the very low C activity in the gas, $10 À14 atm at 750 8C), as was observed 50 years ago for conventional austenitic stainless steel and alloy 600 in only 1 bar CO 2 [22].…”
Section: Introductionmentioning
confidence: 99%